Compact neutron source from head-on collision of high energy density plasma jets - Cui, Ye; Ke, Yan-Zhao; Yang, Xiao-Hu; Ma, Yan-Yun; Shao, Fu-Qiu (Frontiers in Physics, 2022)
We propose a new scheme to generate neutron source with short duration, and the scheme is validated in two-dimensional radiation hydrodynamic simulations. When a laser beam irradiates deuterated polystyrene cone with a half opening angle of 60°, high energy density plasma jets are produced due to the converging effect. As two laser-driven counter-propagating jets collide in a head-on configuration, the kinetic energy converts into internal energy efficiently, inducing a significant increase of density and temperature. Then deuteron-deuteron thermonuclear reactions are triggered and plenty of neutrons are released. The simulation results show that the total neutron yield is as high as 6.6×10^8 with a duration of 103 ps, providing a new way to achieve ultrafast diagnosis with high resolution in experiments.